Off the tenure track: experiences of PhD graduates in academic administrative positions. (3rd July 2022) - Ewing-Cooper, Allison; Gallien, Kathryn N.
ABSTRACT: Advice for PhD graduates seeking to leave academia has proliferated over the last decade, but little attention has been paid to those who continue to work in universities in administrative positions. This study employs a phenomenological qualitative approach to explore the lived experiences of twelve people with PhDs who have taken this alternative career path. Although participants expressed satisfaction with their careers, they also revealed that they faced obstacles to obtaining administrative positions because of misconceptions about the value and purpose of a PhD. The study concludes with policy recommendations for universities and avenues for future research.